6-KADS (KUTCHER ADOLESCENT DEPRESSION SCALE) VERSI BAHASA INDONESIA: ADAPTASI ALAT UKUR - Mutmainnah Sari; Arbianingsih Arbianingsih; Syisnawati Syisnawati; Andi Adriana Amal (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:  The purpose of this study was to adapt the Kutcher Adolescent Depression Scale (6-KADS) measuring instrument.Methods:  The process of adaptation and translation of the Indonesian version of the KADS measurement was carried out according to the procedure for adopting cross-cultural measuring instruments according to Sousa & Rojjanasrirat (2011), namely through 5 stages.Results:  Based on trials on 30 students in Makassar, the reliability coefficient value was 0.75 (reliable). The validity test using the Pearson correlation sig (2-tailed) obtained the value of each item showing a significance value greater than the r table (0.361), which indicates that each question item has good validity. Thus, the results of the adaptation of the 6-item version of the KADS measurement tool can be used in Indonesian adolescents to quickly and easily measure depression in adolescents. This research is still carried out in a small sample, so it is hoped that it can be developed with larger samples. This adapted questionnaire can then be applied in screening for depression in adolescents quickly and easily. Conclusion:  The KADS questionnaire is still underused in Indonesia, and an adapted Indonesian translated version has yet to be available. Therefore the results of this study will provide the final results of a valid and reliable questionnaire which can then be used.